Evaluation of ionomer distribution on porous carbon aggregates in catalyst layers of polymer electrolyte fuel cells - Kayoung Park; Ruijing Gao; Magnus So; Tae Hyoung Noh; Naoki Kimura; Yoshifumi Tsuge; Gen Inoue (Journal of Power Sources Advances, 2022)
Understanding ionomer distribution properties that facilitate proton conduction and oxygen transfer to Pt particles in the cathode catalyst layer (CCL) of the polymer electrolyte fuel cell (PEFC) is essential for optimized design of CCL with high cell performance. In this study, the model structure of Ketjen black (KB) as porous carbon was numerically simulated. After validating the model, the relationship between the weight ratio of ionomer/carbon (I/C) and ionomer coverage was investigated. Moreover, relative proton conductivity of simulated KB was compared with the reference data of Vulcan XC-72 (VB) as non-porous carbon. Under the same I/C ratio conditions, ionomer coverage significantly differed depending on the carbon support. Moreover, under the same carbon volume ratio conditions, simulated KB exhibited lower relative proton conductivity than VB because simulated KB had the lower ionomer volume ratio than that of simulated VB. The relationship between ionomer content and ionomer properties differ depending on the carbon support. The results of our study can contribute to designing an optimal catalyst layer.